1997
DOI: 10.12968/jowc.1997.6.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Crab collagenase in wound debridement

Abstract: A comparative study was performed of the caseinolytic, necrolytic and fibrinolytic activities of a crab collagenase product prepared from the hepatopancreas of the king crab (Paralithodes camtschatica) and four enzyme preparations (trypsin/chymotrypsin and protease complexes isolated from Aspergillus terricola, Carica papaya and pseudomonodaceae). This paper reports an in vitro investigation, an in vivo study with rats and a clinical evaluation. It was found that crab collagenase has the highest proteolytic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 0 publications
0
13
0
2
Order By: Relevance
“…We identified 11 studies that compared collagenase with a petrolatum-based or other ointment, autolytic debridement via a hydrogel or polyacrylate dressing, surgical excision, silver sulfadiazine, and alternative enzymatic agents (papain-urea and trypsin/chymotrypsin) [15][16][17][18][19][20][21][22][23][24][25] (Table 1). Six randomized clinical trials were identified that compared collagenase derived from a bacterial source to a placebo, comprising a heat-inactivated collagenase ointment or a petrolatum-based ointment never charged with the enzymatic agent.…”
Section: ■ Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 11 studies that compared collagenase with a petrolatum-based or other ointment, autolytic debridement via a hydrogel or polyacrylate dressing, surgical excision, silver sulfadiazine, and alternative enzymatic agents (papain-urea and trypsin/chymotrypsin) [15][16][17][18][19][20][21][22][23][24][25] (Table 1). Six randomized clinical trials were identified that compared collagenase derived from a bacterial source to a placebo, comprising a heat-inactivated collagenase ointment or a petrolatum-based ointment never charged with the enzymatic agent.…”
Section: ■ Methodsmentioning
confidence: 99%
“…Boxer and coworkers 15 Lee and Ambrus 16 Varma and coworkers 17 Palmieri and Magri 18 Fu and coworkers 19,c Milne 20 Soroff and Sasvary 21 Konig and coworkers 22 Alvarez and coworkers 23 Glyantsev and coworkers 24 Ozcan and coworkers 25 Pullen et al 25 Collagenase provided more rapid removal of necrotic tissue from the wound bed than placebo…”
Section: Debriding Agent Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparations of collagenolytic enzymes from the Antarctic krill and King Crab species have been successfully evaluated in wound debridement [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Mit aus der Leber und Pankreas von Paralithodes camtschatica (Königskrabbe) isolierter Kollagenase konnte sowohl in vitro als auch in vivo bei Patienten mit Ulcera crurum ein effektives Débridement gezeigt werden [19,43]. Ein kommerziell erhältliches Präparat,das diese Kollagenasen beinhaltet, wurde bislang nicht hergestellt.…”
Section: Effekte Der Kollagenase Auf Die Wundheilungunclassified